2011
DOI: 10.4049/jimmunol.1002845
|View full text |Cite
|
Sign up to set email alerts
|

TLR3-Specific Double-Stranded RNA Oligonucleotide Adjuvants Induce Dendritic Cell Cross-Presentation, CTL Responses, and Antiviral Protection

Abstract: Maturation of dendritic cells (DC) to competent APC is essential for the generation of acquired immunity and is a major function of adjuvants. dsRNA, a molecular signature of viral infection, drives DC maturation by activating TLR3, but the size of dsRNA required to activate DC and the expression patterns of TLR3 protein in DC subsets have not been established. In this article, we show that cross-priming CD8α+ and CD103+ DC subsets express much greater levels of TLR3 than other DC. In resting DC, TLR3 is locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(187 citation statements)
references
References 65 publications
13
174
0
Order By: Relevance
“…These findings support the hypothesis that mammalian cross-presenting DCs, including murine lymphoid CD8 + DCs, murine tissue CD103 + DCs, and the human CD141 lineage, share a common ancestor that has been conserved through evolution in teleost fish. Previous evidence that led other investigators to formulate the hypothesis includes the expression of common transcription factors, such as Batf3 (20,21) and IRF8 (18,19), the sensitivity to TLR3 ligands, and the use of CLEC9A and XCR1 (18,19,(22)(23)(24)29). We were able to identify CLEC9A and XCR1 homologs in trout EST databases, but we showed that the skin CD8 + DC-like subpopulation expressed both Batf3 and IRF8, distinctive transcription factors essential in the development of cross-presenting DCs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These findings support the hypothesis that mammalian cross-presenting DCs, including murine lymphoid CD8 + DCs, murine tissue CD103 + DCs, and the human CD141 lineage, share a common ancestor that has been conserved through evolution in teleost fish. Previous evidence that led other investigators to formulate the hypothesis includes the expression of common transcription factors, such as Batf3 (20,21) and IRF8 (18,19), the sensitivity to TLR3 ligands, and the use of CLEC9A and XCR1 (18,19,(22)(23)(24)29). We were able to identify CLEC9A and XCR1 homologs in trout EST databases, but we showed that the skin CD8 + DC-like subpopulation expressed both Batf3 and IRF8, distinctive transcription factors essential in the development of cross-presenting DCs.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, both populations use the CLEC9A lectin to recognize necrotic cells (22) and express the chemokine receptor XCR1 (23). They also express higher levels of TLR3 than do other DC subtypes and, consequently, are responsive to virus-derived intracellular dsRNAs (24). In humans, a discrete CD141 + (BDCA-3 or thrombomodulin) DC population in blood also exhibits a crosspresenting function (25).…”
Section: Endritic Cells (Dcs) Belong To the Family Of Professionalmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway is involved in type I IFN induction, as in the IPS-1 pathway, but cells expressing TLR3 are limited. The TLR3 distribution profile by flow cytometry confirms its expression in myeloid cells in mice (30). The TICAM-1 pathway converges with the IPS-1 pathway via the molecular complex of IRF-3-activating kinases (38), and therefore activation of the TICAM-1 pathway induces type I IFN and other IFNinducible genes (39).…”
Section: Discussionmentioning
confidence: 61%
“…2). Thus, CD8a + CD11c + DC, which reportedly express TLR3 (30), are the source of type I IFN in PV-infected PVRtg mice.…”
Section: Ticam-1-dependent Type I Ifn Induction By Pv Depends On Mf Imentioning
confidence: 93%